Parallel Engineering Education at Universities and Industries - Mehdi Bahadorinejad; Ali Namaki (آموزش مهندسی ایران, 2008)
To speed up the industrial progress of the country, it is necessary to make vital changes in the engineering education in Iran, so that both students and engineering faculty members are directly involved in the industrial activities of the country. It is also necessary to utilize the expertise of the experienced engineers in the education of engineering students. It is proposed that one of the engineering colleges admit two streams of students, one following the normal education, and the other spending their time both at the university, following the normal education, and in various industries, as related to their respective fields of studies. If the plan is proved to be successful, then the other engineering collogues may implement it. In the parallel plan, the students spend a total of 8 semesters at the university, taking regular engineering courses, and 6 semesters at an industry, working as engineers in training. Any time these students decide to change their stream, they can simply switch to the regular program. In the proposed engineering education plan, emphasis will be placed on engineering creativity and ethics.